Pengaruh Kinerja Lingkungan, Ukuran Perusahaan, Keberagaman Gender Dalam Dewan Direksi, Dan Usia Perusahaan Terhadap Kualitas Pengungkapan Lingkungan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia: The Effect of Environmental Performance, Firm Size, Board Gender Diversity, and Firm Age on Environmental Disclosure Quality in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Mariana Ratih Ratnani; Kuat Waluyo Jati; Fitrarena Widhi Rizkyana; Angellyna Spears Arzetty (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2026)
Environmental information disclosure quality is an important indicator for assessing the level of corporate transparency and accountability regarding the environmental impacts generated by operational activities. In Indonesia, the increasing cases of environmental degradation caused by industrial activities have intensified demands from stakeholders for companies to be more transparent in disclosing information related to their environmental responsibilities. Therefore, this study aims to analyze the influence of environmental performance, firm size, gender diversity on the board of directors, and firm age on the quality of environmental information disclosure among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This research employs a quantitative approach using panel data regression analysis. The research data were obtained from annual reports and sustainability reports published by companies during the observation period. The sampling technique used was purposive sampling, resulting in 61 manufacturing companies that met the research criteria, with a total of 166 observations. Data analysis was conducted using EViews 12 software to examine the relationship between the independent variables and the quality of environmental information disclosure as the dependent variable. The results show that partially, only firm age has a positive and significant effect on the quality of environmental information disclosure. This finding indicates that companies that have operated for a longer period tend to possess greater experience, more established reporting systems, and higher awareness in disclosing environmental-related information. Meanwhile, environmental performance, firm size, and gender diversity on the board of directors do not show significant effects, although they exhibit positive relationships with the quality of environmental information disclosure. These findings imply that corporate experience is one of the key determinants in improving the transparency of environmental information disclosure.